2019
DOI: 10.1002/ana.25408
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea treatment, slow wave activity, and amyloid‐β

Abstract: Obstructive sleep apnea (OSA) increases risk of dementia, a relationship that may be mediated by amyloid‐β (Aβ) and downstream Alzheimer disease pathology. We previously showed that OSA may impair Aβ clearance and affect the relationship between slow wave activity (SWA) and Aβ. In this study, SWA and CSF Aβ were measured in participants with OSA before and 1 to 4 months after treatment. OSA treatment increased SWA, and SWA was significantly correlated with lower Aβ after treatment. Greater improvement in OSA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 19 publications
1
52
0
1
Order By: Relevance
“…Moreover, one recent study indicated that consecutive nights of partial sleep deprivation, with preserved SWS, had no effect on CSF biomarkers for amyloid deposition, neuronal injury, and astroglial activation 40 . More recently, it was shown that OSA treatment increased slow wave activity (SWA) and that SWA was significantly correlated with lower Aβ after treatment 41 . Altogether, these lines of evidence have demonstrated that management of NREM SWS might be a promising target for AD prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, one recent study indicated that consecutive nights of partial sleep deprivation, with preserved SWS, had no effect on CSF biomarkers for amyloid deposition, neuronal injury, and astroglial activation 40 . More recently, it was shown that OSA treatment increased slow wave activity (SWA) and that SWA was significantly correlated with lower Aβ after treatment 41 . Altogether, these lines of evidence have demonstrated that management of NREM SWS might be a promising target for AD prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, patients with OSA obtained worse results in neuropsychological tests of executive functions, such as attention and memory. Importantly, patients with OSA carrying at least one APOEε4 allele, and therefore at risk of develop AD, presented lower scores than those with OSA that do not carry the gene [93]. In this regard, a prospective study with cognitively normal older women showed that those with severe sleep breathing disorder had an increased risk of developing MCI or dementia at follow-up [47].…”
Section: Mechanisms Linking Sleep Respiratory Disorders With Admentioning
confidence: 99%
“…It was associated with sleep fragmentation, daytime sleepiness and significant cardiovascular and metabolic disturbances. Furthermore, OSA might be a risk factor for developing MCI and dementia in the aging population, as it induced cognitive dysfunction in many domains, such as attention, episodic memory, working memory, and executive function [93].…”
Section: Mechanisms Linking Sleep Respiratory Disorders With Admentioning
confidence: 99%
“…In our study, we sought to isolate the effects of obstructive sleep apnea treatment on cerebrospinal fluid (CSF) amyloid‐β (Aβ) from other factors that influence soluble Aβ levels. Most importantly, amyloid plaques are associated with decreased CSF Aβ, particularly Aβ42, due to a probable “sink” effect, whether in symptomatic Alzheimer disease (AD) or during the asymptomatic preclinical phase of AD .…”
mentioning
confidence: 99%